Pengaruh Rekrutmen Dan Pengalaman Kerja Terhadap Prestasi Kerja Karyawan Dengan Penempatan Kerja Sebagai Variabel Intervening Pada PT. Pasoka Sumber Karya Padang - Bayu Sastra Wijaya (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of recruitment and work experience on job performance with job placement as an intervening variable at PT. Pasoka Sumber Karya Padang. The problem addressed in this study is the suboptimal employee performance, which is assumed to be influenced by recruitment quality, work experience, and job placement accuracy. This research employed a quantitative approach with an explanatory research design. The sample consisted of 65 respondents selected using the census technique. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0 software. The results indicate that: (1) recruitment has a positive and significant effect on job performance; (2) work experience positively and significantly affects job performance; (3) recruitment positively influences job placement; (4) work experience positively influences job placement; (5) job placement significantly affects job performance; and (6) job placement mediates the effect of recruitment and work experience on job performance.